A Framework for the Study of Multiple Realizations: The Importance of Levels of Analysis - Overgaard, Morten; Mogensen, Jesper (Frontiers in Psychology, 2011)
The brain may undergo functional reorganizations. Selective loss of sensory input or training within a restricted part of a modality cause “shifts” within for instance somatotopic or tonotopic maps. Cross-modal plasticity occurs when input within a modality is absent – e.g. in the congenitally blind. Reorganizations are also found in functional recovery after brain injury. Focusing on such reorganizations, it may be studied whether a cognitive or conscious process can exclusively be mediated by one neural substrate – or may be associated with multiple neural representations. This is typically known as the problem of multiple realization – an essentially empirical issue with wide theoretical implications. This issue may appear to have a simple solution. When, for instance, the symptoms associated with brain injury disappear and the recovery is associated with increased activities within spared regions of the brain, it is tempting to conclude that the processes originally associated with the injured part of the brain are now mediated by an alternative neural substrate. Such a conclusion is, however, not a simple matter. Without a more thorough analysis, it cannot be concluded that a functional recovery of for instance language or attention is necessarily associated with a novel representation of the processes lost to injury. Alternatively, for instance, the recovery may reflect that apparently similar surface phenomena are obtained via dissimilar cognitive mechanisms. In this paper we propose a theoretical framework, which we believe can guide the design and interpretations of studies of posttraumatic recovery. It is essential to distinguish between a number of levels of analysis – including a differentiation between the surface phenomena and the underlying information processing – when addressing, for instance, whether a pretraumatic and posttraumatically recovered cognitive or conscious process are actually the same. We propose a (somewhat preliminary) system of le